Disrupted Functional Connectivity Within and Between Resting-State Networks in the Subacute Stage of Post-stroke Aphasia - Zhang, Chao; Xia, Yingying; Feng, Tao; Yu, Ke; Zhang, Haiyan; Sami, Muhammad Umair; Xiang, Jie; Xu, Kai (Frontiers in Neuroscience, 2021)
Background Post-stroke aphasia (PSA) results from brain network disorders caused by focal stroke lesions. However, it still remains largely unclear whether impairment is present in intra- and inter-network functional connectivity (FC) within each resting-state network (RSN) and between RSNs in the subacute stage of PSA. Objectives: To investigate the resting-state FC within and between RSNs in patients with PSA and observe the relationships between FC alterations and Western Aphasia Battery (WAB) measures. Methods: Twenty individuals with subacute PSA and 20 healthy controls (HCs) were recruited for fMRI scanning, and only patients with PSA underwent WAB assessment. Independent component analysis was carried out to identify RSNs. Two-sample t-tests were used to calculate intra- and inter-network FC differences between patients with PSA and HCs. The results were corrected for multiple comparisons using the false discovery rate (FDR correction, p<0.05). Partial correlation analysis was performed to observe the relationship between FC and WAB scores with age, gender, mean framewise displacement, and lesion volume as covariates (p<0.05). Results: Compared to HCs, patients with PSA showed a significant increase in intra-network FC in the salience network (SN). For inter-network FC analysis, patients showed a significant increased coupling between left frontoparietal network (lFPN) and SN, and decreased coupling between lFPN and right frontoparietal network (rFPN) as well as between lFPN and posterior default mode network (pDMN) (FDR correction, p<0.05). Finally, a significant positive correlation was found between the inter-group difference of FC (lFPN-rFPN) and auditory verbal comprehension (p<0.05). Conclusions: Altered FC was revealed within and between multiple RSNs in patients with PSA at the subacute stage. Reduced FC between lFPN and rFPN was the key element participating in language destruction. These findings proved that PSA is a brain network disorder caused by focal lesions; besides, it may improve our understanding of the pathophysiological mechanisms of patients with PSA at the subacute stage.